Association Between Workplace Social Capital and Neck Pain: A Cross-Sectional Study Among Workers. Issue 4 (16th April 2022) - Tezuka, Masato; Saeki, Kenta; Nakatsuka, Kiyomasa; Uchida, Kazuaki; Horibe, Kana; Goto, Ryo; Encho, Haruhi; Tamura, Kazuya; Mukaijo, Mao; Yamada, Naoki; Ono, Rei
Abstract : Low overall, bonding, and linking social capital, respectively, had significant associations with presence of neck pain in comparison with each high social capital among workers. Therefore, better management of workplace social capital, especially bonding and linking social capital, may help prevent neck pain among workers. Abstract : Objective: We examined the association between workplace social capital (WSC) and presence of neck pain (NP) among workers. Methods: This cross-sectional study included 595 workers. Presence of NP was assessed using Numerical Rating scale. WSC (overall, bonding, bridging, and linking) was divided into three categories (low, middle, and high) based on tertile distributions. We used logistic regression analysis to investigate the association between WSC and presence of NP. Results: Low overall, bonding, and linking social capital were significantly associated with presence of NP in comparison with each high social capital (overall: adjusted odds ratio [aOR] = 1.76, 95% confidence interval [CI] = 1.14 to 2.73; bonding: aOR = 1.78, 95% CI = 1.19 to 2.67, linking: aOR = 2.18, 95% CI = 1.32 to 3.63). Conclusion: Lower WSC had an association with higher prevalence of NP among workers.